1974
DOI: 10.1002/1097-0142(197403)33:3<611::aid-cncr2820330303>3.0.co;2-u
|View full text |Cite
|
Sign up to set email alerts
|

Therapy with Erwinia l-asparaginase in children with acute leukemia after anaphylaxis to E. coli l-asparaginase

Abstract: Five pediatric leukemia patients being treated with 1‐asparaginase derived from E. coli developed anaphylactic reactions to this enzyme which necessitated discontinuance of the drug. However, further therapy with Erwinia 1‐asparaginase was well tolerated without untoward reactions or toxicities. Three patients achieved complete bone marrow remission (M1) on the 14th day of therapy, one patient achieved partial bone marrow remission (M2), and one had progressive disease. The availability of another active 1‐asp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
12
0

Year Published

1976
1976
2010
2010

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 29 publications
(12 citation statements)
references
References 8 publications
(2 reference statements)
0
12
0
Order By: Relevance
“…4,5,9,15,20 All reacting patients, except for one, reacted to E. coli asparaginase after 10 doses, but those who subsequently reacted to Erwinia asparaginase reacted shortly thereafter, within seven doses. Evans et al 4 observed that the risk of anaphylactoid reactions to Erwinia asparaginase was significantly greater in patients who had previously reacted to E. coli asparaginase, and that the risk of a reaction was related to the total number of asparaginase doses given.…”
Section: Figurementioning
confidence: 99%
“…4,5,9,15,20 All reacting patients, except for one, reacted to E. coli asparaginase after 10 doses, but those who subsequently reacted to Erwinia asparaginase reacted shortly thereafter, within seven doses. Evans et al 4 observed that the risk of anaphylactoid reactions to Erwinia asparaginase was significantly greater in patients who had previously reacted to E. coli asparaginase, and that the risk of a reaction was related to the total number of asparaginase doses given.…”
Section: Figurementioning
confidence: 99%
“…Thus, it is likely that these patients did not have a significantly diminished total L-asparaginase therapeutic effect. 14,15 Pharmacokinetic studies of different L-asparaginase preparations demonstrate that the half-life for the enzyme activity in serum is dependent on the particular enzyme preparation used. 22 The half-life for E. coli L-asparaginase is approximately 1.4 days and for Erwinia L-asparaginase is approximately 0.65 days.…”
Section: Figurementioning
confidence: 99%
“…Thus, it is an acceptable substitute for patients who are allergic to the E. coli protein. [13][14][15] Recently, the Cancer and Leukemia Group B (CALGB) tested a new intensive chemotherapy regimen for adults with untreated ALL. 16 This phase II trial (Study 8811) produced a high rate of complete remissions (85%) and a high proportion of durable remissions in patients from 16 to 80 years old with a median leukemia-free survival (LFS) of 29 months.…”
Section: Introductionmentioning
confidence: 99%
“…[7-9] Erwinia asparaginase has been administered to patients who have experienced allergy to native and polyethylene glycosylated (PEG) E coli asparaginase. [5,10-12] However, there are few published reports regarding the pharmacokinetics, tolerability, and long-term outcomes of children who received Erwinia asparaginase after E coli asparaginase allergy. Additionally, the optimal dosing schedule of Erwinia asparaginase after previous E coli asparaginase allergy remains unclear.…”
Section: Introductionmentioning
confidence: 99%